OPTIMALISASI PETUGAS PENGUMPUL SAMPAH UNTUK PENCEGAHAN PENYEBARAN COVID-19 DI TEMPAT PEMBUANGAN AKHIR (TPA) SUKAWINATAN - Pusnita, Indah; Lubis, Bangun Paruhuman; Mahdiana, Yana; Mayreista, Dita (Aktivasi: Jurnal Pemberdayaan Masyarakat, 2022)
Garbage collector officers are the informal sector in the context of waste management as a whole in a crucial position. the parties that fill the informal sector, namely garbage collectors who work at the Sukawinatan final waste collection site (TPA), to collect waste for processing and sale. Garbage collector officers are involved in selling recyclable inorganic waste because these activities can increase income for them, although this is not proportional to the risk of accidents and disease exposure due to their work as a garbage collector. This service is carried out to find out the economic aspects of the income and work risks of garbage collectors during the pandemic. The results of the socialization are expected that garbage collector officers can prioritize their health during the pandemic so that garbage collectors can avoid the spread of the Covid-19 virus.